Effect of implant connection and restoration design (screwed vs. cemented) in reliability and failure modes of anterior crowns - Freitas Júnior, Amilcar C. [UNESP]; Bonfante, Estevam A.; Rocha, Eduardo Passos [UNESP]; Silva, Nelson R. F. A.; Marotta, Leonard; Coelho, Paulo G. (Wiley-Blackwell, 2011)
The mechanical performance of cemented or screw-retained implant-supported crowns with an internal or external configuration is yet to be understood. This in vitro study evaluated the effect of screw-retained and cement-retained prostheses on internal and external implant-abutment connections. Thereby, the reliability and failure modes of crowns were investigated. Eighty-four implants (Emfils; Colosso Evolution system) were divided into four groups (n = 21 each): screw-retained and internal connection (Si), screw-retained and external connection (Se), cement-retained and internal connection (Ci), and cement-retained and external connection (Ce). Ti-6Al-4V abutments were torqued (30 Ncm) to the implants, and maxillary central incisor metal crowns were torqued (30 Ncm) or cemented (Rely X Unicem; 3M-ESPE) and subjected to accelerated life-testing in water. Use-level probability Weibull curves and reliability for 50,000 cycles at 150 N were calculated. The beta values for Si (1.72), Se (1.50), Ci (1.34), and Ce (1.77) groups indicated that fatigue/damage accumulation accelerated their failure. The Ci group presented the highest reliability, the Se group presented the lowest reliability, and Si and Ce groups presented intermediate reliability. Screw-retained restorations presented mainly abutment fracture. Cement-retained restorations resulted in failures of the screw in the Ce group, but implant/screw fracture in the Ci group.
Keywords: cement-retained; fractography; implant-supported prostheses; reliability; screw-retained